Bearing Capacity Analysis of Spun Pile Foundation in Gas Engine for Electrical Power Plant Project of Selayar - Mutiara, Indra (Politeknik Negeri Ujung Pandang, 2020)
Gas Engine for Electrical Power Plant Project of Selayar is a power plant which will be built in Selayar Regency. This plant uses gas and biodiesel as a fuel. The facilities needed in the power plant construction includes a Gas Engine, Service Water Tank and Biosolar Tank. This study aims to obtain the allowable bearing capacity of the prestressed spun pile foundation for the three buildings based on soil investigation data of SPT (Standard Penetration Test) at BH-1 (gas engine), BH-2 (service water tank) and BH-3 (biosolar tank). The Meyerhof formula is used for the calculation of ultimate bearing capacity analysis on prestressed spun piles with various diameters for each depth. Calculation of the allowable bearing capacity (Qa) of the foundation at a depth of 19 meters, using a spun pile with a diameter of 300 cm, obtained a Qa value of 94.17 tons at BH-1, 94.20 tons at BH-2, and 74.65 tons at BH-3. Using a spun pile with a diameter of 400 cm, the Qa values were 116.71 tons on BH-1, 117.64 tons on BH-2, and 91.92 tons on BH-3. Using a spun pile with a diameter of 500 cm, the Qa values were 168.67 tons on BH-1, 172.09 tons on BH-2, and 131.49 tons on BH-3. Meanwhile, the values of Qa obtained were 229.85 tons on BH-1, 236.66 tons on BH-2, and 177.79 tons on BH-3 with the use of a spun pile with a diameter of 600 cm.